The investigation of OSHA indexes and the pattern of work-related accidents at the Mazandaran wood and paper industry between 2007 and 2013 - M Mououdi; M Shabani; A Hassani (طب کار)
Introduction: Currently,work-related accidentsas the thirdcause of deathin the world, the second leading causeof death inIranandone of the mostimportantriskfactorshealth, social,economicandindustrialsocietiesaredeveloping. Incidentasone of theindustryhasbeenincorruptivepotential. Methods:Thestudywaslongitudinal. Registration formsforaccidentevaluatework related accidentspersonnelwere86-91years. IncidentsrecordedtoevaluatetheindicatorssuchasOSHA(F.R), (S.R), (F.S.I), (A.R),(I.R), (coefficient T-safe), (UCL & LCL), (LTC), (LWD) were used .ThanSPSS version17for analysisandchi-squaretestandoddsratioswere used. Result: Total numberof incidentsrecordedwas218counts. Repeat thehighestratein88incidents(3.019),the coefficient ofrepeatability-Severity(1.088),the maximumvalueofT-safe ratio(9.53), respectively.Scale(UCL & LCL)withstandardvalues(UCL & LCL)showed thatevery88 years respectively0.166and8.49respectively.Thisyear،the highestCoefficient(LWD),(LTC), (A.R)and(I.R)to(391.94), (1.68), (3.65%) of(0.000015) found.Theseageplaceaccidentswithpv =0.002 employment statusand location oftheeventwithpv =0.023 incidenttypeand location of theeventwithpv=0.000monthandtype ofeventpv =0.009 age andtype of eventwithpv =0.021placeor type of accidentwithpv=0.00was significant. Discussion:Recordssystemeventstoresponsiveindustry'scurrent formwithoutinvestigating the causesofaccidents. Usingappropriatemethodstoprevent,reduceorlimittheconsequencesoftakethe necessary measuresare. Some of the majorstrategiesproposedforachieving this goalinclude:Continuouseffectivetrainingof personnel, supervise carefully howdoing the right thingtodotorunaregularprogramindividual.